Assessment of Activating Reservoir Emergency Storage in Climate-Change-Fueled Extreme Drought - Chae, Heechan; Ji, Jungwon; Lee, Eunkyung; Lee, Seonmi; Choi, Youngje; Yi, Sooyeon; Yi, Jaeeung (Water (Switzerland), 2022)
With exacerbating climate change, the current reservoir storage capacity in South Korea is insufficient to meet the future scheduled water demand. No study has yet evaluated the effects of applying the water supply adjustment standard (Standard) and activating the reservoir emergency storage in response to extreme drought. The main objective is to assess the effects of applying Standard and activating emergency storage in meeting the water demand under extreme drought at six multipurpose reservoirs (Andong, Gimcheon-Buhang, Gunwi, Hapcheon, Imha, and Milyang) in the Nakdong River Basin, South Korea. We built a reservoir simulation model (HEC-ResSim), determined the extreme drought scenarios, and emergency storage capacity. We evaluated three reservoir operation cases (general operation, regular Standard, and revised Standard) from 2011 to 2100. The results show that applying the Standard and activating the emergency storage are effective in meeting the future water demand during extreme drought. In conclusion, we need to secure 110 million cubic meters (MCM) (Hapcheon reservoir) and 8 MCM (Gunwi reservoir) of water to reduce the number of days in the emergency stage. This research serves as a fundamental study that can help establish Standard and emergency storage activation criteria for other multipurpose reservoirs in preparation for extreme drought.
Keywords: 'current; Emergency storages; Extreme drought; Multipurpose reservoirs; Nakdong river basins; Reservoir emergency storage; Reservoir operation; South Korea; Water demand; Water supply adjustment standard; climate change; extreme drought; Nakdong River Basin; reservoir emergency storage; reservoir operation; water supply adjustment standard